Editor’s Note - Kozak-Oxnard, Andrea M. (Columbia Journal of Gender and Law, 2016)
In honor of our twenty-fifth anniversary, we have assembled this special Anniversary Issue to chronicle the Journal’s evolving zeitgeist. The first essay in this Issue, written by our co-founder Caroline Fredrickson, recounts the Journal’s aspirational beginnings and the ever-changing role of women in the law, and urges us to remember how much work we still must do to achieve gender justice. The second essay, by Professor Patricia Williams, considers emerging medical technologies and the difficult questions and deep concerns they pose for gender norms, reproductive practices, and bodily autonomy. Finally, this Issue showcases three papers and an accompanying introductory piece arising out of a panel on abortion and travel. The papers highlight a critical gender issue facing this generation on a global scale—the literal lengths to which women often must go in order to vindicate critical reproductive rights. These papers are authored by Joanna N. Erdman, Yasmine Ergas, and Madeline M. Gomez, and are introduced by the panel organizers, Lisa Kelly and Nicole Tuszynski. A heartfelt thank you to all the CJGL staffers, editors, authors, and readers—past and present—who have made the Journal such a success over the past quarter century. You have made this world a wiser and more just place. Here’s to the next twenty-five years and beyond! Sincerely, Andrea M. Kozak Editor-in-Chief, 2016–2017 Columbia Journal of Gender and Law